Influences of customer-based brand equity and destination competitiveness on destination loyalty in Malaysia - Wong, Philip Pong Weng (2014)
Many countries are heavily dependent on tourism receipts as a major source of foreign revenue, especially in the developing nations in the south-east Asian region such as Thailand, Indonesia, and Malaysia. Tourism and its related activities are often used as a catalyst for economic growth and development for many cities and towns located in this region and is also an effective tool for the reduction of poverty and the improvement of living standards for many of their residents. Among the methods utilized to increase the competitiveness level of the destinations that are promoted, branding is regarded as an important strategy by tourism management organizations to differentiate their country, state, or city from competing destinations. A destination which possess a positive brand equity and strong competiveness attributes will have an advantage over their competitors in attracting a bigger share of the tourists’ market and, furthermore, visiting tourists will probably stay longer and will have a tendency to spend more on tourism related services when they are in the destination. This study seeks to evaluate the brand equity and competitiveness levels of selected urban destinations in Malaysia and also to examine the relationships between the constructs of customer-based brand equity (CBBE), destination competitiveness (classified into functional and abstract attributes), and destination loyalty. This thesis can be considered a pioneer study in exploring the possibility of categorizing the destination competitiveness construct into the components of functional and abstract attributes using the Delphi technique. The research framework was validated by confirmatory factor analysis through structural equation modeling (SEM). A non-probability sampling technique is employed in this study. The sample was chosen from international tourists comprising different nationalities, who have visited and stayed at least one night, in the cities of Kuala Lumpur, Penang, Melaka, Kota Kinabalu, and Kuching. The survey was conducted over a period of approximately four months (from January, 2013-April, 2013), and the questionnaires were distributed to tourists with the assistance of tour operators, hoteliers, and tourist information centers located in Kuala Lumpur, Penang, Melaka, Kota Kinabalu, and Kuching. In addition to the English version, the questionnaire was also translated into Chinese and Arabic. Results from this study indicate that the construct of destination competitiveness can indeed be divided into the two components of functional and abstract attributes and confirms the mediating roles of CBBE in the relationship between functional and abstract attributes, and also the indirect effect that CBBE has on destination loyalty via abstract attributes. Functional attributes has been found to be the antecedent of CBBE while abstract attributes are influenced by CBBE. Path analysis of the structural model also supports the hypothesized relationships between the constructs of CBBE,destination competitiveness (functional and abstract attributes), and destination loyalty. In terms of practical implications, findings from this study will help destination management organizations (DMOs) to assess the brand equity and competitiveness levels of the selected destinations, and can be used to identify their strengths and weaknesses in relation to their competitveness and brand equity levels. This will assist the DMOs in developing more effective branding strategies for their destinations,leading to increased tourist arrivals and tourist spending.